2017
DOI: 10.4102/hsag.v22i0.1013
|View full text |Cite
|
Sign up to set email alerts
|

An elderly, urban population: Their experiences and expectations of pharmaceutical services in community pharmacies

Abstract: Experiences and expectations Community pharmacyFace-to face interview Researcher-designed structured questionnaire a b s t r a c t Objective: The aim of this study was to determine the pharmaceutical services experiences of an elderly, urban population in relation to their expectations in community pharmacy.Design: and setting: The study was a cross-sectional descriptive empirical study and was conducted by means of a structured questionnaire, designed and administered by the researcher, in face-to-face interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This significant finding could be due to two-third of our patients being in the middle age group and older. These older patients are more vulnerable and have higher expectations of care to service their medicine-related needs due to more chronic diseases compared to the younger generation [ 25 ]. This previous study also concluded that the expectations of their elderly population on pharmacy services was not met in terms of discussion on the other medicine on their chronic medicine and issues of medicines left from previous visits.…”
Section: Discussionmentioning
confidence: 99%
“…This significant finding could be due to two-third of our patients being in the middle age group and older. These older patients are more vulnerable and have higher expectations of care to service their medicine-related needs due to more chronic diseases compared to the younger generation [ 25 ]. This previous study also concluded that the expectations of their elderly population on pharmacy services was not met in terms of discussion on the other medicine on their chronic medicine and issues of medicines left from previous visits.…”
Section: Discussionmentioning
confidence: 99%